The Monetary Approach to the Exchange Rate : Rational Expectations, Long-Run Equilibrium and Forecasting - MacDonald, Ronald; Taylor, Mark. (Washington, D.C. : International Monetary Fund, 1992)
We re-examine the monetary approach to the exchange rate from a number of perspectives, using monthly data on the deutschemark-dollar exchange rate. Using the Campbell-Shiller technique for testing present value models, we reject the restrictions imposed upon the data by the forward-looking rational expectations monetary model. We demonstrate, however, that the monetary model is validated as a long-run equilibrium condition. Moreover, imposing the long-run monetary model restrictions in a dynamic error correction framework leads to exchange rate forecasts which are superior to those generated by a random walk forecasting model.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet